ANALISIS EFEKTIFITAS PERIKLANAN SEPEDA MOTOR SUZUKI NEX DENGAN MENGGUNAKAN METODE EPIC MODEL - Ari Setiawan (2013)
This study entitled "Analysis of advertising effectiveness motorcycle Suzuki Nex models using the EPIC" aims to investigate the effectiveness of advertising Suzuki nex based EPIC model method (Emphaty, Persuasion, Impact, Communication). Object of this study is the Student Universitas Pembangunan Nasional "veteran" Jakarta has ever seen, heard or seen ads on television commercials Suzuki nex. There were 100 respondents who participated in this study. The sampling technique used was convenience sampling method. EPIC in terms of dimensions, it was found that the Suzuki ad nex effective enough to influence the customers living in South Jakarta, among the 4 dimensions, communication is the most dominant factor that can be seen from the figure IV.4.1. The results achieved in this study is expected to be a material consideration for the company's progress and useful for writers as well as those reading this paper.